Kesiapan Digitalisasi Akuntansi Koperasi dalam Menerapkan SAK Entitas Privat - Eka Setiajatnika; Udin Hidayat (LPPM Universitas Koperasi Indonesia, 2026)
The adoption of the Financial Accounting Standards for Private Entities (SAK EP) by cooperatives after the issuance of the Regulation of the Minister of Cooperatives Number 2 of 2025 demands more than mere normative adherence, as it also requires sufficient operational preparedness. This study seeks to conceptually analyze the readiness of accounting digitalization within cooperatives in supporting the implementation of SAK EP. Employing a qualitative approach with a literature-based research design, the study examines accounting standards, regulatory provisions, and relevant scholarly literature. The analysis reveals that accounting digitalization readiness in cooperatives constitutes a multidimensional framework comprising technological readiness, human resource capabilities, organizational support, and regulatory alignment. Collectively, these dimensions shape the capacity of cooperatives to implement SAK EP in a consistent and sustainable manner. From a conceptual perspective, accounting digitalization plays a strategic role in enhancing the quality of cooperative financial reporting, particularly with respect to accuracy, timeliness, and information traceability. This study enriches the literature on cooperative accounting and offers policy-oriented insights for strengthening financial governance in cooperatives.